Tailoring carbon nanotubes surface chemistry for the purification of antileukemic drugs - Barros, Maria A. (2020)
Biopharmaceuticals have been used to overcome fatal diseases related with aging. L-aspariginase (LA), in particular, has shown evidences of being efficient for leukemia therapy. The LA production and purification require several steps increasing the cost of the process. In this work, functionalized carbon nanotubes (CNTs) were studied as a cost-effective support to purify LA. It was shown that CNTs have strong affinity for the target biopharmaceutical, meaning that can be a promising alternative for the adsorption and purification of LA.